Efficacy of herbal medicines in treatment of respiratory infections - Karkinski, Dimitar; Stoshevski, Bojan; Angelovska, Irina; Poposka, Biljana; Nakova Krstikj, Olivera; Pejkovska, Sava; Manusheva, Nancy; Velikj Stefanovska, Vesna; Dokikj, Dejan (Macedonian Association of Anatomists and Morphologists, 2024)
Introduction. Herbal medicine forms the basis of modern pharmacy, and hence, it has much to offer to patients suffering from common, acute bronchitis and flu. The aim of this study was to investigate the efficacy of the herbal medicines Broncho Protect and Andrographis Extract as dietary supplements against standard medical treatment in patients with proven acute upper and/or lower respiratory tract infection. Thisprospective, double-blind, randomization study was conducted at the PHI University Clinic for Pulmonology and Allergology in Skopje. Forty patients with clinical symptoms of acute upper and/or lower respiratory tract infection were included. Patients were randomized into two groups; the first group received standard therapy without restrictions plus placebo and the second group which, in addition to standard therapy, received Bronho Protect and Andographis extract. The results of patients' self-assessment of their health status indicated a statistically significant improvement in both groups, but no difference in the final outcome. The results of the assessment of patients’ health status by the doctors indicated that in the group that received herbal medicines all patients gotbetter. Also, auscultation findings were significantly better in patients who were treated with herbal medicines. Herbal medicines are effective in treatment and prevention of respiratory infections and provide a much-needed alternative to ineffective antibiotics, whereby patients feel they are receiving beneficial therapy, thus reducing their tendency to use antibiotics.
Keywords: herbal medicines; respiratory infections